Tainted blood transfusion in hospitals: a study of the law governing hospital's, blood bank's and blood donor's liability towards blood recipients / Aznyda Yaakub and Azreen Syaheeda Hasnudin - Yaakub, Aznyda; Hasnudin, Azreen Syaheeda (Faculty of Law, 2007)
This research paper will discuss on current situation of tainted blood transfusions in Malaysia and the law governing this matter. We will look into the liability of the Hospitals, blood banks and the donors. We will also conduct both medical and legal researches to find out the real problem and means to solve them. Having regards to the present situation, we will discuss several cases which have taken place in Malaysia and also the relevant local laws pertinent to this matter. For example, the law on professional negligence as well as laws regarding the spreading of infectious diseases as provided in our local statutes. As part of our research, we will conduct several interviews with different parties both from the medical as well as legal field to obtain information regarding this issue. An analysis of the interviews conducted will be provided. In addition, we will also conduct a comparative study between the laws relevant to this issue in other countries such as United States of America, Australia as well as India in comparison with our Malaysian law. At the end of the research, we will provide recommendations and conclusion on the issue of blood transfusions.